A LTERNATIF KAPAL PENGANGKUT LPG MELALUI SUNGAI DENGAN MEMANFAATKAN TEKNOLOGI ISO-TANK - Muis, Abdul (Badan Pengkajian dan Penerapan Teknologi, 2006)
Condition of Indonesian rivers, geographically, is sharp, narrow, and shallow shape with many curves and also high water current with big differences in water tidal. Moreover, there are hard sedimentation in estuary caused big affect to vessel entering harbour. With great potential on LPG carrier passing through river, required limited draft, length and capacity of vessel. An Advanced container technology, also design to carry liquid (ISO-TANK), may distribute LPG through the river only by conventional container carrier. Self Propulsion Barge is an alternative of ISO-TANK carrier with small draft and big capacity.